Does Monetary Policy Affect the Stability of Islamic Banks? - Savon, Zakaria (International Journal of Economics and Financial Issues, 2025)
The financial crisis of 2007-2008 compelled economists to reevaluate the impacts and trajectories of monetary policy. It highlighted the new challenges central banks face, particularly in integrating financial stability into the monetary policy-making process. Financial stability is closely connected to monetary policy. The financial sector plays a vital role as a channel for monetary policy to affect the real economy. Numerous studies have investigated the impact of monetary policy on the stability of conventional banking institutions. Nonetheless, a substantial study vacuum persists concerning the impact of monetary policy on the stability of Islamic financial institutions. Our research aims to investigate this matter. The study analyzed a sample of 34 financial institutions across 11 countries with dual banking systems, spanning the years 2013-2022. It utilized a random effects estimator and a system GMM estimator. The findings demonstrate a substantial and negative impact of the monetary policy rate on the stability of Islamic banks. The study’s conclusions have significant consequences, especially for infrastructure and monetary policy. The advancement of the Islamic money market signifies a crucial development in the strength and expansion of Islamic financial organizations. Furthermore, monetary policymakers must evaluate the effects of interest rate-oriented monetary policy on the stability of Islamic banks.